Electronic personnel document management: from legal experiment to practice - S. Yu. Golovina; L. V. Zaytseva (Правоприменение, 2022)
The subject. The introduction of electronic technologies into management processes has led to the need to regulate the issues of the use of electronic personnel document management (further - EPDM). In the spring of 2020, Russia was conducting a legal experiment on the use of electronic documents related to work. As part of this experiment, according to the rules established by federal law, individual employers voluntarily refuse to issue certain types of personnel documents in paper form. It concerned employment contract and other contracts with an employee (on financial responsibility, apprenticeship), a vacation schedule, employee statements, as well as regulatory and organizational and administrative documents of the employer on labor (orders on admission, dismissals, penalties, etc.). The results of this experiment became the basis for the introduction of appropriate amendments to the Labor Code of the Russian Federation.The main purpose of the study is to develop recommendations for improving the current labor legislation for the legalization of electronic personnel document management as part of a system of measures to achieve the maximum balance of interests of employees and employers.The main methods of the research are the analysis and generalization of judicial practice on labor disputes related to the evaluation of electronic evidence, the practice of using electronic personnel document management by individual employers, both participating and not participating in the legal experiment conducted at the federal level.The main results, scope of application. The preliminary results of above mentioned experiment have been summarized and an assessment of the validity and potential effectiveness of the draft law submitted to the Russian Federal Assembly has been given. The authors propose the results of a critical analysis of the interim results of the legal experiment on the introduction of EPDM. The authors demonstrate the pros and cons of electronic document management in terms of the readiness of the current legislation for it, as well as subjects of labor relations. The innovations of the prepared draft law on the introduction of a new article 22.1 to the Russian Labor Code as well as its positive aspects and some shortcomings are considered. Not only legal and technical shortcomings are indicated, but also some fundamental substantive contradictions. For example, a negligent attitude to the involvement of employees in making managerial decisions in the social and labor sphere due to the establishment of a trade union monopoly in a number of issues of social dialogue when introducing electronic personnel document management. The draft law does not consistently address issues related to security, enhanced qualified signature and the costs associated with obtaining it by an employee. The modern attitude of Russian courts to electronic evidence in labor disputes is demonstrated by the example of judicial practice. These examples demonstrate the most pressing issues of the introduction and use of EPDM, which need to be resolved at the legislative level. There is a need for effective protection of all participants in labor relations in the context of the development of digital technologies and their implementation in the daily life of each person.Conclusions. Adoption of new federal law regulating EPDM was necessary to establish general rules for employee-employer interaction in the digital environment, as well as for legalization of the exchange of electronic documents as a way of labor management.